2003
DOI: 10.1097/00002030-200306130-00003
|View full text |Cite
|
Sign up to set email alerts
|

Structural defects and variations in the HIV-1 nef gene from rapid, slow and non-progressor children

Abstract: Our results suggest a link between nef gene functions and the progression rate in HIV-1-infected children. Moreover, non-progressor-associated variations in the core domain of Nef, together with the genetic analysis, suggest that nef gene evolution is shaped by an effective immune system in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 42 publications
6
50
1
Order By: Relevance
“…On the other hand, due to the large variability of the nef gene, functional studies on a single allelic variant, although containing representative amino acid variations, may greatly constrain the analysis of possible Nef phenotypes in a given patient. This is why in a previous study we isolated and sequenced a large number of nef alleles sequentially derived from perinatally infected children with different progression rates: six nonprogressors (NPs), three slow progressors (SPs), and four rapid progressors (RPs) (8). We found that a higher proportion of disrupted sequences were derived from NPs compared to the other patients.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…On the other hand, due to the large variability of the nef gene, functional studies on a single allelic variant, although containing representative amino acid variations, may greatly constrain the analysis of possible Nef phenotypes in a given patient. This is why in a previous study we isolated and sequenced a large number of nef alleles sequentially derived from perinatally infected children with different progression rates: six nonprogressors (NPs), three slow progressors (SPs), and four rapid progressors (RPs) (8). We found that a higher proportion of disrupted sequences were derived from NPs compared to the other patients.…”
mentioning
confidence: 81%
“…Patients' characteristics as well as isolation and subcloning of patients' nef genes are described elsewhere (8). Briefly, we studied 13 perinatally HIV-1-infected children of Italian origin showing different modality of disease progression: six NPs, three SPs, and four RPs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, data from in vitro studies also show an association of CD4 down-modulation with disease progression: Nef alleles from HIV strains isolated from patients with progression to AIDS efficiently down-regulate CD4, whereas Nef alleles from HIV strains isolated from longterm nonprogressors are compromised in their ability to down-modulate CD4. [15][16][17][18] Importantly, the progressive CD4 down-modulation on CD4 þ T cells in HIV þ patients may contribute to the functional impairment of CD4 þ T cells observed in HIV infection. 39 CD4 plays an essential role in the generation of adaptive immune responses by acting as a coreceptor with the T cell receptor/CD3 complex, which binds peptide-MHC complexes.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Furthermore, Nef alleles from HIV strains isolated from patients with progression to AIDS efficiently down-regulate CD4, whereas Nef alleles from HIV strains isolated from long-term nonprogressors are ineffective in down-modulating CD4. [15][16][17][18] The well-known CD4 down-regulation by HIV in vitro is mediated by the viral proteins Nef, Env, and Vpu. 19 explanations have been proposed for why CD4 downmodulation favors HIV, including attenuation of CD4 signaling that might decrease viral transcription, prevention of superinfection, and enhancement of virion release.…”
Section: -10mentioning
confidence: 99%